A PRODUÇÃO DA VERDADE: CRIMES SEXUAIS EM IRATI-PR (1931-1950) - Ribas Filho, Marcelo Douglas Nascimento (2020)
Based on judicial documents from the Irati County, in the southeast of Paraná, and on the time cut of 1931 to 1950, we intend to analyse the fined truths in sexual crimes. The medical-legal ritual movement, in these cases, was to establish standards of evaluation from the subjects and situations, in intention of controling bodies and sexuality, besides to discipline the daily experiences of men and, especially, women. Throught the qualitative investigation of defloration, seduction and rape processes, we seek to apprehend the nature and organization of these judicial files and the constant conflicts within the acts, permeated by several titles and personified speeches in the figure of different subjects: experts, scribes, deputies, discrict attorneys, lawyers, judges, witnesses, defendants and victims. Inspired by Michel Foucault, we study the discursive themes from the involved people's declarations that disputed the legitimacy about the incident in an uneven space of the production of the truth: based, mainly, in the distrust regarding the victim's word.